Tinggal Serumah Dengan LGBT: Satu Diskusi Menurut Perspektif Syarak: Living Together with LGBT: A Discussion from the Sharia Perspective - Mohd Azhar Abdullah; Nur Azwani Mansor; Abdul Azib Hussain; Muhammad Lukman Ibrahim; Khairulnazrin Nasir (RABBANICA - Journal of Revealed Knowledge, 2024)
Living together with individuals who identify as lesbian, gay, bisexual, or transgender (LGBT) demands significant consideration, particularly when they cohabit as partners. The promotion of LGBT ideologies alongside social media advancements and human rights advocacy has led to an increasing prevalence of same-sex relationships. Some youth in Malaysia have embraced LGBT as a modern, liberated lifestyle. They engage in intimate relationships, including cohabitation between gay or lesbian partners, as though they were married couples, disregarding religious boundaries and moral values. The public often remains indifferent to such cohabitation due to the assumption that it involves individuals of the same gender. While there is extensive research on gender identity disorders among LGBT individuals, which covers aspects such as contributing factors, influences, psychology, and rehabilitation, there is limited discourse from a Sharia perspective on the legality and implications of cohabitation. This study uses a qualitative method to look at the basics of Islamic law in this area. Specifically, it looks at the possible dangers of slander (fitnah) and how the principle of sadd zara’i (blocking the means) can be used to stop immoral acts. The strength of this research is supported by evidence that unrestricted social interactions can lead to negative psychological impacts and deviant behaviours. The primary objective of this study is to provide an in-depth understanding of the Sharia prohibitions against same-sex intimate relationships. Additionally, the study proposes Sharia-compliant guidelines for situations where individuals may cohabit with LGBT persons. Tinggal satu rumah dalam kalangan kelompok gay, lesbian, biseksual, trasgender (LGBT) perlu diberikan perhatian serius, sementelah apabila mereka berkesedudukan. Pergaulan luar tabii antara pasangan sejenis semakin berkembang. Ideologi LGBT digerakkan seiring kemajuan media sosial dan perjuangan prinsip-prinsip hak asasi kemanusiaan (human rights). Sebahagian remaja dan belia di Malaysia telah terpengaruh dengan LGBT yang dianggap sebagai gaya hidup moden dan bebas. Mereka menjalankan hubungan intim, termasuk tinggal serumah dengan gay atau lesbian seperti suami isteri. Mereka tidak mempedulikan batasan agama dan nilai moral. Sebahagian masyarakat bersikap acuh terhadap pasangan luar tabii yang tinggal serumah kerana persamaan jantina. Terdapat banyak kajian berkaitan kecelaruan jantina kelompok LGBT dari sudut faktor, pengaruh, psikologi dan pemulihan. Namun, perbincangan menurut perspektif hukum syarak, mereka tinggal dalam satu rumah belum diperincikan kajiannya. Menggunakanaedah kajian kualitatif, kajian ini meninjau asas-asas syarak, khususnya sejauh mana tahap kemungkinan fitnah dan keperluan pemakaian kaedah sadd zara’i bagi menutup pintu-pintu kemungkaran. Kekuatan kajian disokong oleh faktor pergaulan bebas yang menyumbang kepada psikologi negatif dan perlakuan luar tabii. Tujuan utama kajian adalah memberikan kefahaman yang mendalam tentang tegahan syarak tentang bahayanya hubungan sama jantina. Selain itu, kajian iniengemukakan garis panduan syarak bagi seseorang lelaki atau perempuan tinggal serumah dengan golongan LGBT.